Genome-Wide Identification and Analysis of the NF-Y Gene Family in Potato (Solanum tuberosum L.) - Liu, Zhen; Li, Yuanming; Zhu, Jinyong; Ma, Wenjing; Li, Zhitao; Bi, Zhenzhen; Sun, Chao; Bai, Jiangping; Zhang, Junlian; Liu, Yuhui (Frontiers in Genetics, 2021)
Nuclear factor Y (NF-Y) is a ubiquitous transcription factor in eukaryotes, which is composed of three subunits (NF-YA, NF-YB, and NF-YC). NF-Y has been identified as a key regulator of multiple pathways in plants. Although the NF-Y gene family has been identified in many plants, it has not been reported in potato (Solanum tuberosum). In the present study, a total of 41 NF-Y proteins in potato (StNF-Ys) were identified, including 10 StNF-YA, 22 StNF-YB, and nine StNF-YC subunits, and their distribution on chromosomes, gene structure, and conserved motif was analyzed. A synteny analysis indicated that 14 and 38 pairs of StNF-Y genes were orthologous to Arabidopsis and tomato (Solanum lycopersicum), respectively, and these gene pairs evolved under strong purifying selection. In addition, we analyzed the expression profiles of NF-Y genes in different tissues of double haploid (DM) potato, as well as under abiotic stresses and hormone treatments by RNA-seq downloaded from the Potato Genome Sequencing Consortium (PGSC) database. Furthermore, we performed RNA-seq on white, red, and purple tuber skin and flesh of three potato cultivars at the tuber maturation stage to identify genes that might be involved in anthocyanin biosynthesis. These results provide valuable information for improved understanding of StNF-Y gene family and further functional analysis of StNF-Y genes in fruit development, abiotic stress tolerance, and anthocyanin biosynthesis in potato.